Shipping stock returns and shipping factors : an investigation for the US listed firms before and after the 2008 financial crisis - Neophytou, Rita Areti (Department of Commerce, Finance and Shipping, Faculty of Management and Economics, Cyprus University of Technology, 2018)
This paper investigates the influence of the financial factors of leverage, dividend yield and market value and of the shipping factors of newbuilding prices, freight rates and bunker prices, on the stock returns of the listed shipping companies in US. The paper examines the period between 2003 and 2018, dividing this period into the following sub-periods: the pre-financial crisis period 2003-2008 (including the financial crisis year 2008) and the post-financial period 2009-2018. The main findings of this paper show that the financial crisis altered the effect of some of these variables on the shipping stock returns. The market value, the newbuilding prices, the freight rates and the bunker prices seemed to have a positive impact on the shipping stock returns before the financial crisis, dividend yield has a negative impact and the leverage ratio does not have any significant impact. On the other hand, after the financial crisis the impact of the leverage ratio on the shipping stock returns became significant and positive while the impact of the dividend yield, newbuilding prices and freight rates became insignificant. Hence before the financial crisis the shipping stock returns were explained mainly from the shipping factors, where after the financial crisis they were explained mainly from financial factors.
Keywords: Shipping stock returns; Leverage ratio; Dividend yield; Market value; Newbuilding prices; Earnings per day; Bunker prices; Financial crisis